Managing talent across advanced and emerging economies: HR issues and challenges in a Sino-German strategic collaboration. Issue 20 (12th November 2016) - Stokes, Peter; Liu, Yipeng; Smith, Simon; Leidner, Sarah; Moore, Neil; Rowland, Caroline
Abstract : The human resource (HR) practices involved in global talent management continue to advance and evolve. A majority of talent management commentary is from multinational corporation (MNC) perspectives. However, the less commented small-to-medium-sized enterprise (SME) also confronts challenges grounded in economic (i.e. resources, finance), organisational (i.e. size, scope and structure) and consequent behavioural rationales (i.e. mindsets and stances). This paper establishes and examines a number of propositions which consider how these factors impact on an advanced economy SME's talent management in emerging economy collaborations. An interpretive qualitative methodology is employed using interviews conducted within two cases – SME and an MNC comparator case. The SME case is used as the driving force of the paper and its theoretical focus and findings. The MNC is used to develop issues as a comparator case. The findings show SME economic and organisational drivers producing behavioural dynamics in relation to mimesis of planned actions yet informal serendipitous responses in reality; a predilection for the proximate and familiar; design configurations of short-term expatriate visits and inpatriates; cumulating in ongoing inpatriate acculturisation and re-acculturation oscillation. Consequently, the implication is that the SME needs a HR practices encompassing resignation to the situation, flexibility and resilience in order to survive and progress.